Use of extracorporeal membrane oxygenation in an awake patient after a major trauma with an incidental finding of tuberculosis. (May 2016) - Haneke, F; Schildhauer, TA; Strauch, J; Swol, J
We report the use of extracorporeal membrane oxygenation (ECMO) in a trauma patient with an incidental finding of open tuberculosis (TB). Sedation was reduced during extracorporeal support and awake veno-venous ECMO was successfully performed. Subsequently, accidental cannula removal caused major blood loss which required the administration of cardiopulmonary resuscitation (CPR). Our case report demonstrates that the incidental finding of open TB is an important hint for differential diagnosis and that it should still be considered in high-income countries. In addition, awake ECMO appears to be a feasible therapeutic option in non-transplant patients, although the described case demonstrates that patient compliance and nursing care are important for therapeutic success to avoid complications, for example, inadvertent decannulation.